PERFECTION OF THE TECHNOLOGY AND EQUIPMENT FOR REALIZATION OF THE PROCESS ROLLING-DIVISION - V. I. Timoshpolskij; N. V. Andrianov; S. M. Zhuchkov; A. N. Bondarenko; V. A. Tishchenko; L. V. Kulakov (Литьë и металлургия, 2004)
The development of metallurgical branch in current conditions stipulates the necessity of increasing of the technological processes efficiency of the rolled products production, which provide economy of energy resources, reduction of building costs of the new and reconstruction of operating plants. Tendency to enlargement of the primary part for small-section and wired mills, connected with transfer to continuous casting, arouses the necessity of their reconstruction for the purpose of increasing of discharge ability